2-d stability of the Néel wall - DeSimone, Antonio; Knüpfer, Hans; Otto, Felix (Calculus of variations and partial differential equations, 2006)
We are interested in thin-film samples in micromagnetism, where the magnetization m is a 2-d unit-length vector field.